2017
DOI: 10.1016/j.dhjo.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Extra costs of living with a disability: A review and agenda for research

Abstract: More quantitative evidence is needed using rigorous methods, for instance evidence based on longitudinal data and as part of policy evaluations. More internationally comparable data on disability is required for the quantitative evidence to develop, especially in low- and middle-income countries where studies are scarce. Qualitative and participatory research is also needed, especially to investigate unmet needs, and the consequences of extra costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
169
1
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(211 citation statements)
references
References 20 publications
7
169
1
10
Order By: Relevance
“…Yet emerging evidence suggests that people with disabilities may face additional challenges accessing these types of schemes. For example, with means testing, eligibility thresholds rarely consider extra disability‐related costs, which can alter determinations of who is considered to be poor (Banks et al, ; Gooding and Marriot, ; Mitra et al, ). One study in Viet Nam found that consideration of disability‐related costs would increase the poverty rate among people with disabilities from 16.4 per cent to 20.1 per cent (Braithwaite and Mont, ), which would have important implications if programmes were means tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet emerging evidence suggests that people with disabilities may face additional challenges accessing these types of schemes. For example, with means testing, eligibility thresholds rarely consider extra disability‐related costs, which can alter determinations of who is considered to be poor (Banks et al, ; Gooding and Marriot, ; Mitra et al, ). One study in Viet Nam found that consideration of disability‐related costs would increase the poverty rate among people with disabilities from 16.4 per cent to 20.1 per cent (Braithwaite and Mont, ), which would have important implications if programmes were means tested.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, targeted programmes may be needed to address disability‐specific concerns, such as access to assistive devices and specialist health and educational services. Account also must be made for the higher costs incurred by people with disabilities in participating in society, as a result of needs for accessible transport, carers, assistive devices and so on (ILO, ; Devandas Aguilar, ; Mitra et al, ). According to recent estimates from the International Labour Organization, 27.8 per cent of people with severe disabilities globally receive some form of disability benefit (ILO, ).…”
Section: Introductionmentioning
confidence: 99%
“…Two recent systematic reviews support the existence of a positive association between disability and poverty (Banks, Kuper, & Polack, ; Mitra, Palmer, Kim, Mont, & Groce, ), beginning to fill the gap of quantitative research on the disability–poverty relationship, especially for low‐ and middle‐income countries. Critical scholars point out the danger embedded within the impulse to codify, measure, and transport “two such multidimensional and continually evolving ‘conditions’ of life” across different cultural contexts: namely, the danger of perpetuating a “simplified discourse,” akin to that circulating for women in development (WID) projects that ignored the agency and capacities of the women themselves (Campbell, ; Grech, , p. 222).…”
Section: Querying Disability Querying Development: Shared Theoreticamentioning
confidence: 99%
“…At work we use the concept of lifestyle in disability (Mitra et al, 2017;Sharma and Maiumdar, 2009;Ventegodt and Merrick, 2003). We have assumed that lifestyle is a complex process that refers to a social group -people with a similar degree and type of disability.…”
Section: Introductionmentioning
confidence: 99%